ALASAN TURKI MEMBERIKAN DUKUNGAN DIPLOMATIK DAN MILITER KEPADA AZERBAIJAN TERKAIT KONFLIK DI NAGORNO KARABAKH TAHUN 2020 - Ananda, Febrina Ruri; Sushanti, Sukma; Parameswari, Anak Agung Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2022)
This study aims to describe the reasons for Turkey providing diplomatic and military support to Azerbaijan during the Nagorno Karabakh conflict in 2020 using descriptive qualitative methods. Turkey's active involvement in the Nagorno Karabakh conflict through diplomatic and military support to Azerbaijan is not only controversial but has triggered protests from the international community. Turkey is the only country that has been found to provide open military support. Turkey's military support makes national leadership often neglect regional security and stability in the conflicted regions. However, Turkey as a country needs energy supplies from Azerbaijan. This research then finds that Turkey has a national interest to protect and secure the international pipeline infrastructure that carries oil and natural gas from Azerbaijan to its own territory. Energy security is also further related to Turkey's ambition to become an energy transit center between regions within the framework of the Southern Gas Corridor. Kata Kunci: Turkey, Azerbaijan, Energy Security, Nagorno Karabakh Conflict